Brown algae as winners: Divergent resilience to high light under acidified conditions shapes macroalgal communities around a carbon dioxide vent - Zhang, Di; Wada, Shigeki; Hall‐Spencer, Jason; Gao, Kunshan (Wiley, 2026)
To investigate the effects of ocean acidification (OA) on macroalgae, we conducted in situ surveys along a natural CO2 vent gradient in Shikine Island, Japan, together with complementary laboratory culture experiments. The in-situ surveys revealed that near the CO2 vent (where pH dropped by 0.37), macroalgal diversity and species-richness were less than half those at the reference sites under ambient pH conditions. Nevertheless, the rates of CO2 assimilation of several common macroalgae increased from the reference site to the areas near the CO2 vent. This enhancement coincided with decreased photosynthetic CO2 affinity, reflecting that the acidified area down-regulated CO2-concentrating mechanisms in the algae. Measured photosystem II activity revealed that macroalgae at reference sites had lower electron transport rate and light utilization efficiency. The laboratory culture experiments, in which the dominant species (Gelidium elegans and Dictyopteris undulata), were cross-exposed to ambient and elevated CO2 conditions, further demonstrated that the stress near the CO2 vent significantly exacerbated photoinhibition under high light stress. Our results demonstrate that reduced pH and high sunlight act synergistically to impair macroalgal photosynthesis through exacerbated photoinhibition. This effect was more pronounced in red algae (e.g., G. elegans) than in brown algae (e.g., D. undulata). These different physiological responses provide a mechanistic explanation for an observed community shift, from red algal dominance in ambient pCO2 areas to brown algal dominance near the vent. Our findings imply that future OA, when combined with high-light stress, may selectively disadvantage high-light-sensitive species, thereby altering macroalgal community structure in coastal waters.